Clinical Parameters to Predict Future Clinical Disease Activity After Treatment Change to Higher-Dose Subcutaneous Interferon Beta-1a From Other Platform Injectables in Patients With Relapsing-Remitting Multiple Sclerosis - Novotna, Martina; Tvaroh, Ales; Mares, Jan (Frontiers in Neurology, 2020)
Objective: To identify predictors of clinical disease activity after treatment optimization to higher-dose interferon beta-1a in relapsing-remitting multiple sclerosis (MS). Methods: This was a retrospective-prospective observational multicenter study. We enrolled patients with at least one relapse on platform injectable therapy who were changed to 44µg interferon beta-1a. Our primary endpoint was the clinical disease activity-free (cDAF) status at 6, 12, 18 and 24 months. Secondary endponts included relapse-free status and disability progression-free status at different timepoints. The primary predictor of interest was the monosymptomatic vs polysymptomatic index relapse, based on the number of affected functional systems from the Kurtzke scale during the last relapse prior to baseline. Analysed secondary predictors of clinical disease activity we based on different demographic and relapse characteristics. Kaplan-Meier estimates of the cumulative probability of remaining in cDAF status were performed. The time to clinical disease activity was compared between groups using univariate Kaplan-Meier analysis and multivariate Cox regression. Multivariate analyses were processed in the form of CART (Classification & Regression Trees). Results: The proportion of patients in cDAF status was 84.7%, 69.5%, 57.5% and 54.2% at 6, 12, 18, and 24 months. After 2 years of follow-up, 55.9% of patients remained relapse-free and 87.8% of patients remained disability progression-free. At all timepoints, the polysymptomatic index relapse was the most significant predictor of clinical disease activity of all studied variables. Hazard ratio of cDAF status for patients with monosymptomatic vs polysymptomatic index relapse was 1.94 (95% CI 1.38-2.73). CART analyses also confirmed the polysymptomatic index relapse being the strongest predictor of clinical disease activity, followed by higher number of pre-baseline relapses with the most significant effect in the monosymptomatic index relapse group. The next strongest predictors of clinical disease activity were cerebellar syndrom as the most disabled Kurtzke functional system for the monosymptomatic relapse group, and age at first MS symptom ≥45 for the polysymptomatic relapse group. Conclusions: Patients with a polysymptomatic index relapse and/or higher number of relapses within two years prior to baseline are at high risk of clinical disease activity, despite treatment optimization from platform injectable therapy to higher-dose interferon beta-1a.